2012
DOI: 10.1111/j.1553-2712.2012.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Interunit Transitions of Care Between Emergency Physicians and Hospital Medicine Physicians: A Conceptual Approach

Abstract: Patient care transitions across specialties involve more complexity than those within the same specialty, yet the unique social and technical features remain underexplored. Further, little consensus exists among researchers and practitioners about strategies to improve interspecialty communication. This concept article addresses these gaps by focusing on the hand-off process between emergency and hospital medicine physicians. Sensitivity to cultural and operational differences and a common set of expectations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 48 publications
0
54
0
Order By: Relevance
“…The potential for health information technology redesign to enhance communication and coordination during care transitions is high, decreasing reliance upon unstructured and chaotic communication channels that require additional time and energy. 19,51 Although requiring time, resources, and cultural change, these methods may help minimize unnecessary and time-consuming efforts to locate providers and interruptions in workflow, thereby increasing work quality and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for health information technology redesign to enhance communication and coordination during care transitions is high, decreasing reliance upon unstructured and chaotic communication channels that require additional time and energy. 19,51 Although requiring time, resources, and cultural change, these methods may help minimize unnecessary and time-consuming efforts to locate providers and interruptions in workflow, thereby increasing work quality and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Risks include less verbal exchange and the failure to convey subtle patient information because of presumed review of the electronic medical record. (42)…”
Section: Transforming Emergency Care For Older Adultsmentioning
confidence: 99%
“…The current study demonstrated improved resident satisfaction following implementation of a standardized TOC signout guide which follows currently published best practice recommendations as reported by Beach et al (2012).Our evidence suggests that a TOC sign-out system may be implemented in a large, tertiary care children's hospital with improved resident satisfaction. In addition, a specific need was identified in residency education related to ED specific TOC sign-outs.…”
Section: Resultsmentioning
confidence: 52%